Analysis of Intake Performance of Forebody and Inlet on Pre-deformation. (1st March 2023) - Li, Siyi; Liu, Lei; Liu, Shenshen; Yang, Xiaofeng; Wang, Ziyi; Du, Yanxia
Abstract: Under long cruise conditions, the forebody and inlet of a hypersonic vehicle were sensitive to deform under the aerodynamic thermal load, which hurt aerodynamic characteristics, intake performance, and aircraft safety. A pre-deformation method was proposed by using the numerical method of fluid-thermal-structural coupling based on the in-house software, aiming at the static deformation of a typical forebody-inlet model. Three pre-deformed models were combined by the forebody/inlet deformation and then compared the intake performance between the pre-deformed models and the ideal rigid model. The results show that the pre-deformation of the forebody can not only ensure the intake performance partly but also avoid the risk of excessive pressure on the intake wall. The pre-deformation of the inlet can reduce the flow separation near the ramp wall and reduce the pressure of intake, but it also reduces the total pressure recovery coefficient and affects intake performance negatively.